SINTESIS KALKON TURUNAN PIRIDIN DARI ASETILTIOPEN DAN PIRIDINKARBALDEHID SERTA UJI ANTIOKSIDAN MENGGUNAKAN METODE DPPH - Indah Fitria Ningsih; Nur Balatif; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The compounds of condensation reaction have been synthesized using microwave irradiation with a base catalyst and their antioxidant activity were evaluated. One of the result of synthesized compounds was (4-hydroxy-2,6-di(pyridin-3-yl)-4-(thiophen-2-yl) cyclohexane-1,3-diyl) bis (thiophen-2-ylmethanone) (IF). The structure of the synthesizedproduct has been elucidated using IR, 1H-NMR, 13 1 C-NMR, mass-spectroscopic data and elemental analysis. The final product was screened for its antioxidant activity. The compound exhibited low DPPH (2,2’-diphenyl-1-picrylhydrazyl) scavenging activity which gave IC50 value > 500 ppm.